MANUSIA SEBAGAI KHALIFAH, SELFMANAGEMENT DALAM HADITS - Arif Wahyudi; Suraijiah; Fahmi Riady; Rusdiana (Adisam Publisher, 2026)
This article discusses the concept of humans as khalifah and its connection to self-management from the perspective of the hadith. The findings indicate that the role of humans as khalifah is not only spiritual in nature but also has practical implications in daily life, particularly in self-management and social responsibility. The hadith of the Prophet Muhammad (peace be upon him) emphasizes that every individual is a leader who will be held accountable, making self-management the primary foundation for fulfilling this trust. Self-management involves the effective management of time, emotions, and resources. This study is also supported by empirical findings showing that self-management skills contribute to increased productivity and quality of life. Thus, the integration of Islamic values and self-management skills is key to realizing humanity’s role as responsible and effective khalifah.